Applying a Transnational Approach to the Question of Irish Home Rule: Ireland, New Zealand and Home Rule - Pauline Collombier-Lakeman (Revue Française de Civilisation Britannique)
The paper aims to examine the Home Rule question as a debate, which triggered an interest and some discussions beyond the borders of Ireland and the United Kingdom. Through the example of New Zealand, a British settlement colony, which enjoyed self-governance and had welcomed an Irish diaspora, the paper will attempt to shed light on several important facts. First, Irish communities settled abroad were a source of financial and moral support for the Irish Parliamentary Party and for the Irish organisations campaigning for Home Rule for Ireland. Secondly, like Canada or Australia, New Zealand was a colonial precedent, which Irish Home Rulers used to legitimize their demand for self-government. Lastly, the Home Rule issue also allowed New Zealanders to ponder over their own issues, such as their place within the British Empire and their identity.